2005
DOI: 10.1038/sj.cgt.7700850
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for hepatocellular carcinoma using sonoporation enhanced by contrast agents

Abstract: We examined whether sonoporation enhanced by a contrast agent (BR14) was effective in gene therapy for hepatocelluar carcinoma (HCC). Human hepatic cancer cells (SK-Hep1) and plasmid cDNAs expressing green fluorescent protein (GFP), interferonb (IFNb), and LacZ were used. In vitro, SK-Hep1 cell suspensions with DNA and BR14 were sonoporated. Expressions of every plasmid cDNA and the antitumor effect of IFNb were analyzed. In vivo, GFP and IFNb genes with BR14 were directly injected into subcutaneous tumors usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 38 publications
0
56
0
1
Order By: Relevance
“…Most in vivo studies have concentrated on organs and tissues that are readily imaged by diagnostic ultrasound machines, including skeletal muscle, heart and kidneys. 35,36,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Table 1 summarizes the results of some recent studies in these tissues using reporter genes, 35,36,[48][49][50][51][52][53][54]58,60,61 and broadly similar data have begun to emerge from studies in the vascular, 4,63,64 neurology 65-67 and oncology 18,37,68 fields, the pancreas 69 and in hematology. 70 On first inspection the relatively modest enhancements in plasmid-mediated transfection after USE in vivo may appear disappointing compared with the results obtained in vitro.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 79%
See 2 more Smart Citations
“…Most in vivo studies have concentrated on organs and tissues that are readily imaged by diagnostic ultrasound machines, including skeletal muscle, heart and kidneys. 35,36,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Table 1 summarizes the results of some recent studies in these tissues using reporter genes, 35,36,[48][49][50][51][52][53][54]58,60,61 and broadly similar data have begun to emerge from studies in the vascular, 4,63,64 neurology 65-67 and oncology 18,37,68 fields, the pancreas 69 and in hematology. 70 On first inspection the relatively modest enhancements in plasmid-mediated transfection after USE in vivo may appear disappointing compared with the results obtained in vitro.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 79%
“…Table 2 summarizes some recent examples using animal models and therapeutic transgenes that have potential clinical relevance. 4,37,55,56,69,70 Although these and other in vivo studies provide proofof-concept that UEGT can indeed achieve therapeutically effective gene transfer, the delivery approaches used (e.g. direct injection of plasmid/MCB into the liver or left ventricular cavity, UEGT requiring temporary cessation of blood flow in target organs) are in many cases unattractive for clinical use, certainly if repeat administrations for chronic conditions are contemplated.…”
Section: Multiple Biophysical Effects Of Ultrasound May Contribute Tomentioning
confidence: 99%
See 1 more Smart Citation
“…These qualities mean that BR14 may be a better agent in sonoporation-mediated transfection. Indeed, recent studies have indicated that BR14 effectively enhanced sonoporation-based gene transfection into hepatic cancer implant in mice [21] as well as into saphenous vein graft in porcine [22].…”
mentioning
confidence: 99%
“…Although use of a viral vector for gene therapy leads to more efficient transfection, several studies have noted reservations regarding immune response and mutagenesis with viral infection. [2][3][4] However, Sakakima et al 5 recently reported results showing that gene therapy with ultrasonication may become a new and safe treatment for hepatocellular cartinoma. Ultrasonication techniques have been used in vivo and in vitro to load antiproliferating agents, oligonucleotides, proteins and plasmid DNA into cells, as well as for an efficient nonviral approach, 1,6,7 whereas others have reported the efficiency of the 'sonoporation' method for gene therapy.…”
Section: Introductionmentioning
confidence: 99%